IoT-Based Smart Home Door Lock Security System Using ESP32 - Wong, Sy Hui; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2024)
Security has always been a paramount aspect in society. Traditional physical keys have always been used to secure doors but it still comes with some inconveniency and vulnerabilities despite it being the most ordinary technology until now. Each key is dedicated to a particular lock, necessitating the need for individuals to carry multiple keys for different doors. In the traditional key-based system, the burglars may exploit the weakness using the specialized tools and techniques to break into the house. Nowadays, there has been a shift towards incorporating modern innovations for enhanced security with the advancement in Internet of Things (IoT) technology. Automatic door locks have gained popularity in the industry as they offer improved protection for valuables and personal safety. This project is built upon the ESP32 as the backbone of the security system, in which it coordinates with the user to control the door locking mechanism. Result from the prototype suggests that the user could control the locking system seamlessly through the Telegram application. On top of that, the log data could be seen by the user in a readable manner in the Blynk application in real time. The achievement of this project conclude that the employment of IOT enables safety and convenience of home user in a single system is possible nowadays.